Building Moderate Millennial Muslims Through Sufistic Multicultural Da'wah - Yasin, M. (IAIN Ponorogo, 2024)
This study aims to analyze the role of Sufistic multicultural da'wah in shaping the moderate character of the millennial Muslim generation during the challenges of the digital era. Using a qualitative research method based on literature studies, this study explores the Sufistic da'wah approach that emphasizes the value of spirituality and appreciation for diversity. Data is collected from relevant academic literature and analyzed systematically to identify da'wah's challenges in the era of information technology globalization. The results of the study show that Sufistic multicultural da'wah can provide strategic solutions in dealing with the issue of intolerance and radicalism through internalizing the values of moderation, social harmony, and local wisdom. This finding emphasizes the importance of Sufistic da'wah in building a generation of Ull Albab who not only understand moderate Islamic values but are also able to contribute to the harmony of a multicultural society. Future research recommendations include the development of a multicultural da'wah model based on the participation of the millennial generation, as well as the evaluation of the effectiveness of the Sufistic approach in the context of a multicultural society.